The effects of flow settings during high-flow nasal cannula support for adult subjects: a systematic review - Li, Jie; Albuainain, Fai A.; Tan, Wei; Scott, J. Brady; Roca, Oriol; Mauri, Tommaso (Critical care (London, England), 2023)
During high-flow nasal cannula (HFNC) therapy, flow plays a crucial role in the physiological effects. However, there is no consensus on the initial flow settings and subsequent titration. Thus, we aimed to systematically synthesize the effects of flows during HFNC treatment. In this systematic review, two investigators independently searched PubMed, Embase, Web of Science, Scopus, and Cochrane for in vitro and in vivo studies investigating the effects of flows in HFNC treatment published in English before July 10, 2022. We excluded studies that investigated the pediatric population (< 18 years) or used only one flow. Two investigators independently extracted the data and assessed the risk of bias. The study protocol was prospectively registered with PROSPERO, CRD42022345419. In total, 32,543 studies were identified, and 44 were included. In vitro studies evaluated the effects of flow settings on the fraction of inspired oxygen (F O ), positive end-expiratory pressure, and carbon dioxide (CO ) washout. These effects are flow-dependent and are maximized when the flow exceeds the patient peak inspiratory flow, which varies between patients and disease conditions. In vivo studies report that higher flows result in improved oxygenation and dead space washout and can reduce work of breathing. Higher flows also lead to alveolar overdistention in non-dependent lung regions and patient discomfort. The impact of flows on different patients is largely heterogeneous. Individualizing flow settings during HFNC treatment is necessary, and titrating flow based on clinical findings like oxygenation, respiratory rates, ROX index, and patient comfort is a pragmatic way forward.